2014
DOI: 10.1007/s12035-014-8644-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated Mutations of TDP-43 Promote Turnover of the Protein Through the Proteasomal Pathway

Abstract: TAR DNA-binding protein (TDP-43) is a major component of most ubiquitin-positive neuronal and glial inclusions of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). A number of missense mutations in the TARDBP gene have been identified in patients with familial and sporadic ALS, as well as familial FTLD with ALS. In the diseased states, TDP-43 proteins exhibit characteristic alterations, including truncation, abnormal phosphorylation, and altered subcellular distribution. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Next, we investigated the mechanism of HSF1‐mediated protection against stress‐induced insolubility of TDP‐43. Accumulation of TDP‐43 into ubiquitin‐positive inclusions in ALS and frontotemporal lobar degenerated (FTLD) brains have implicated the UPS in TDP‐43 degradation or pathogenesis (Araki et al, ; Liu et al, ). We used a GFP reporter system that allowed us to quantify global rates of UPS proteolysis (Dantuma et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated the mechanism of HSF1‐mediated protection against stress‐induced insolubility of TDP‐43. Accumulation of TDP‐43 into ubiquitin‐positive inclusions in ALS and frontotemporal lobar degenerated (FTLD) brains have implicated the UPS in TDP‐43 degradation or pathogenesis (Araki et al, ; Liu et al, ). We used a GFP reporter system that allowed us to quantify global rates of UPS proteolysis (Dantuma et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Chloroquine inhibits autophagy by inhibiting the acidification of autophagosome and maturation of autolysosome, resulting in the accumulation of autophagic vesicles and the inhibition of autolysosomal protein degradation. The pharmacological inhibition of autophagy by chloroquine has been previously tested in in vitro models of ALS, but to date no data has been registered in skeletal muscle cells[ 38 ]. After treating with chloroquine the explants from skeletal muscles, significant LC3-II increased levels were observed, suggesting that autophagy was still activated.…”
Section: Discussionmentioning
confidence: 99%
“…The ALS-associated mutations in UBQLN2 cause impaired autophagy and induce increased overall TDP-43 levels and promote the TDP-43 aggregation in the neuronal cells (Osaka et al, 2016). Araki et al have found that the disease-associated TDP-43 mutants like G298S and A382T, are more rapidly turned over than the wild-type protein, through the ubiquitin-proteasome system, thus highlighting the pathological relevance of the TDP-43 proteolysis and clearance (Araki et al, 2014).…”
Section: Emerging Mechanisms Of Tdp-43-induced Cytotoxicitymentioning
confidence: 99%